2022
DOI: 10.1002/pbc.30175
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of delayed childhood cancer care in low‐ and middle‐income countries: A systematic review

Abstract: Early access to care is essential to improve survival rates for childhood cancer. This study evaluates the determinants of delays in childhood cancer care in low‐ and middle‐income countries (LMICs) through a systematic review of the literature. We proposed a novel Three‐Delay framework specific to childhood cancer in LMICs by summarizing 43 determinants and 24 risk factors of delayed cancer care from 95 studies. Traditional medicine, household income, lack of transportation, rural population, parental educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…1 We previously conducted a systematic review to summarise the drivers of delays in childhood cancer care in LMICs. 5 Our findings suggested that cultural, socioeconomic, and demographic factors had the most substantial effect across the entire continuum of care. However, our review did not evaluate how these factors affect mortality from childhood cancer.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…1 We previously conducted a systematic review to summarise the drivers of delays in childhood cancer care in LMICs. 5 Our findings suggested that cultural, socioeconomic, and demographic factors had the most substantial effect across the entire continuum of care. However, our review did not evaluate how these factors affect mortality from childhood cancer.…”
Section: Introductionmentioning
confidence: 61%
“…We used findings from our previous systematic review as the theoretical framework to identify key determinants of delays in care for children with cancer in LMICs and aligned our methodology to the WHO CureAll framework as well as the socio-ecological model (SEM). 5 , 7 , 8 In brief, childhood cancer was defined as all-inclusive cancers according to the International Classification of Childhood Cancer, third edition. 9 Studies with a sample population older than 18 years or from high-income countries were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…(4) For pediatric cancer, the second delay is associated with higher rates of morbidity and mortality and can be influenced by health service capacity and referral systems at smaller health centers. (2,10) This second delay can also be impacted by similar sociocultural factors described in the first delay. (4,10) The final delay is concerned with delays experienced once reaching the definitive medical center where diagnosis and treatment services can be provided.…”
Section: Introductionmentioning
confidence: 94%
“…(2,10) This second delay can also be impacted by similar sociocultural factors described in the first delay. (4,10) The final delay is concerned with delays experienced once reaching the definitive medical center where diagnosis and treatment services can be provided. While not always contained within the framework, we have included financial influences within each of these delays to highlight the economic toll of pediatric cancer care.…”
Section: Introductionmentioning
confidence: 99%
“…Many children with cancer in LMICs face barriers across the entire continuum of care, particularly for delays in diagnosis and initiation of treatment. 6 Children often do not have access to high-quality care and have high rates of abandonment of treatment. 7 These barriers lead to increased mortality risks, financial costs, and household impoverishment.…”
Section: Introductionmentioning
confidence: 99%